Do student leaders in NTU exhibit similar personality traits? - Tan, Chia Loong. (2008)
The objective of our research is to first, revalidate the ‘Big Five’ personality construct and second, establish the relationship between personality and the leadership effectiveness of student leaders in NTU. Our findings validated the personality construct and provided support for the Trait Leadership perspective.